Reprogramming of fibroblasts intoinduced Pluripotent Stem Cells – iPSC : hepatitis C – challenges and progress - Oliveira, Catarina Alexandra Grilo de (2017)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2013